ﺍﻟﺮﺩ ﻋﻠﻰ ﻣﻨﻜﺮ ﺍﻟﻤﻌﺎﺩ ﻓﻲ ﺍﻟﻘﺮﺁﻥ ﺍﻟﻜﺮﻳﻢ (Journal of the College of Basic Education, 2022)
Praise be to God who ended through death the hopes of the Caesars, and I testify that there is no god but God alone, with no partner.And I bear witness that our Master Muhammad is His servant and His Messenger, he fulfilled the trust, conveyed the message, advised the nation, and through him God revealed The tone, and he was confused in conveying the message and answering the call of God, Glory be to Him, until certainty came to him.And after: The Resurrected: A great pillar from the pillars of faith, without which faith is valid, and there is no doubt about it that if